Paternal self-efficacy for promoting children's obesity protective diets and associations with children's dietary intakes - Adam D. Walsh; Kylie D. Hesketh; Jill A. Hnatiuk; Karen J. Campbell (BMC, 2019)
Abstract Objective Fathers' parenting behaviours contribute to the development of children's dietary behaviours and subsequent weight outcomes, yet the majority of research focusses on maternal influences. Understanding fathers' perceptions of their effectiveness to influence children's dietary behaviours will allow the development of whole-of-family interventions promoting obesity protective behaviours. This unique study is the first to investigate 1) tracking of paternal self-efficacy for promoting obesity protective dietary intakes in young children; 2) demographic characteristics of fathers and their self-efficacy category; and 3) associations between paternal self-efficacy and young children's dietary intakes. Methods Paternal self-efficacy for promoting children's obesity protective dietary intakes was assessed longitudinally from fathers (n = 195) in the Extended Infant Feeding Activity and Nutrition Trial Program at child age 4 and 36 months. Multinomial logistic regression examined self-efficacy tracking categories (persistently high; persistently low; increasing; decreasing) by paternal age, education and BMI. Linear regression examined associations between paternal self-efficacy tracking categories and child dietary intakes at 36 months. Results Paternal self-efficacy for promoting children's obesity protective dietary intakes reduced over time. Fathers with trade/certificate or university qualifications had lower odds of having persistently low/decreasing self-efficacy (97 and 87% lower respectively) compared to high-school educated fathers. Positive associations (β (95% CI)) were observed between paternal self-efficacy category and children's dietary intakes at 36 months: increasing self-efficacy and fruit (β89.8 (6.8; 172.7)), and vegetables (β39.2 (12.2; 66.2)); persistently high self-efficacy and water (β69.1 (2.9; 135.1)); decreasing self-efficacy and non-core drinks ((β30.1 (10.1; 50.1)). Persistently high self-efficacy was negatively associated with non-core drinks (β-20.2 (− 34.8; − 5.5)), with negative associations observed between decreasing self-efficacy and children's intakes of fruit (β − 49.9 (− 87.5; − 12.3)), vegetables (β-19.9 (− 31.7; − 8.2)) and water (β-92.4 (− 172.6; − 12.3)). Conclusions Higher and/or sustained paternal self-efficacy is associated with fathers' education and is important in promoting children's obesity protective dietary intakes. Associations between paternal self-efficacy and children's dietary intakes are present at a young age. This investigation was unique in its focus on paternal self-efficacy for promoting children's obesity protective dietary intakes and associations with children's dietary intakes. Future family interventions should consider how to maintain and/or improve paternal self-efficacy to promote obesity protective intakes from early childhood.